Cavitary lung metastases of mixed metaplastic breast cancer mimicking aspergilloma - Clara So; Takeshi Ushigusa; Torahiko Jinta (Thoracic Cancer, 2023)
Abstract We report a case of a 57‐year‐old woman with pulmonary metastasis of breast cancer presenting with a characteristic cavitary shadow resembling aspergilloma. The primary tumor and metastases showed multiple histopathologic components, including squamous cell carcinoma. Although a fungal ball‐like shadow may indicate the presence of a pulmonary aspergilloma, a comprehensive examination, including bronchoscopy, should be considered.